Adaptive Load Balancing in Cloud Computing Environment - Waghmode , Santosh T.; Patil , Bankat M. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The cloud computing platform load balancing is one of the challenge. Effective or efficient resource use in the cloud environment also known as load balancing became an important concern with the cloud computing platform’s rapid development in users and their need for a variety of services. In order to enhance network capacity and reduce response time, load balancing play is important role in storage system. Our primary goal is to provide a novel load balancing method that, by combining efficient scheduling and cloud - based techniques, can balance incoming requests load from users across the world that are located in various regions to get data from distributed data sources. In addition to effectively utilizing cloud resources and improving task processing times, also worked on develop a dynamic load balancing algorithm that also ensures elasticity in a cloud environment. Divisible weighted round-robin, round-robin, and weighted least connection alorithm are the primary load balancing algorithms discussed in this paper.